INDONESIA’S MARITIME DEFENCE PARADIGM SINE QUA NON GLOBAL MARITIME FULCRUM - Hidayat, Safril; Sidhha, Arlan (The Republic of Indonesia Defense University, 2018)
Maritime security and maritime safety cannot be separated from the world's maritime fulcrum policy. Policies relating to maritime security and safety are not only related to the Indonesian Navy but also involve other major components, reserve components and supporting components in the national defense system. Maritime defense requires policies, regulations, measures, and operations that are different from conventional national defense strategy. This research used qualitative design perspective validated through triangulation process. This research finds that the threats stretching from the West to East and from the North to South of Indonesia require synergy and integration of all components of the nation. Therefore, it is necessary to refocus policies, regulations, measures, and operations in the maritime defense system